3D Kinematic of Bunched, Medium and Elongated Sprint Start - Slawinski, J.; Dumas, R.; Cheze, L.; Ontanon, G.; Miller, C.; Mazure-Bonnefoy, A. (International Journal of Sports Medicine, 2012)
The aim of this study was to test the influence of 3 different horizontal distances between the blocks (bunched, medium and elongated) on the velocity of the centre of mass (VCM) and the kinetic energy (KE) of the body segments and of the whole body. 9 well-trained sprinters performed 4 maximal 10 m sprints. An opto-electronic Motion Analysis® system (12 digital cameras 250 Hz) was used to collect the 3D trajectories of 63 markers during the starting block phase. The results demonstrated that the elongated start, compared to the bunched or medium start, induced an increase of VCM at block clearing (2.89±0.13; 2.76±0.11; 2.84±0.14 m.s − 1) and a decrease of the performance at 5 and 10 m. Both results were explained by a greater pushing time on the blocks in the elongated condition. During the starting block phase, the KE of the whole body was greater in the elongated start (324.3±48.0 J vs. 317.4±57.2 J, bunched and 302.1±53.2 J, medium). This greater KE of the whole body was mainly explained by the KE of the head-trunk segments. Thus, to improve the efficiency of the starting block phase, the athlete must produce greater KE of the head and trunk segments in the shortest time.
Keywords: sprint; running; performance; start; biomechanics